The high-cycle fatigue fracture mechanism and fatigue strength prediction of compacted graphite iron. (August 2022) - Zou, C.L.; Pang, J.C.; Qiu, Y.; Liu, R.; Li, S.X.; Jing, G.X.; Xu, C.G.; Zhang, Z.F.
Highlights: The tensile strength, yield strength and fatigue strength of CGI decrease with increasing the temperature. The fatigue strength of CGI is mainly influenced by the competitive mechanism of matrix strength and damage localization. A prediction model for the fatigue strength of CGI was established. Abstract: The tensile properties, high-cycle fatigue (HCF) properties and corresponding fatigue fracture mechanism of compacted graphite iron (CGI) were investigated. It is found that the tensile strength, yield strength and fatigue strength of CGI decrease as the temperature increases. At 25 °C, the fatigue cracks of CGI are mainly caused by local cleavage fracture at ferrite around the tip of vermicular graphite. At 400 °C and 500 °C, the gradual occurrence of grain boundary softening and oxidation may reduce the difficulty of fatigue crack propagation. Similar to temperature, the change of microstructure content also has a significant effect on the fatigue properties of CGI. By analyzing the damage characteristics of fatigue fracture morphology, it is shown that the fatigue crack initiation of CGI is mainly dependent on the damage localization caused by the ferrite and vermicular graphite inside the graphite cluster and the pearlite and spheroidal graphite outside the graphite cluster under cyclic loading. Based on those results, a fatigue strength prediction model associated with tensile strength, yield strength and microstructure area percentage was proposed. This model can provide a reasonable prediction of HCF strength of CGI at different temperatures.